High‐Performance Electrochemical NO Reduction into NH3 by MoS2 Nanosheet. Issue 48 (27th October 2021) - Zhang, Longcheng; Liang, Jie; Wang, Yuanyuan; Mou, Ting; Lin, Yiting; Yue, Luchao; Li, Tingshuai; Liu, Qian; Luo, Yonglan; Li, Na; Tang, Bo; Liu, Yang; et al.
Abstract: Electrochemical reduction of NO not only offers an attractive alternative to the Haber–Bosch process for ambient NH3 production but mitigates the human‐caused unbalance of nitrogen cycle. Herein, we report that MoS2 nanosheet on graphite felt (MoS2 /GF) acts as an efficient and robust 3D electrocatalyst for NO‐to‐NH3 conversion. In acidic electrolyte, such MoS2 /GF attains a maximal Faradaic efficiency of 76.6 % and a large NH3 yield of up to 99.6 μmol cm −2  h −1 . Using MoS2 nanosheet‐loaded carbon paper as the cathode, a proof‐of‐concept device of Zn‐NO battery was assembled to deliver a discharge power density of 1.04 mW cm −2 and an NH3 yield of 411.8 μg h −1  mgcat. −1 . Calculations reveal that the positively charged Mo‐edge sites facilitate NO adsorption/activation via an acceptance–donation mechanism and disfavor the binding of protons and the coupling of N−N bond. Abstract : MoS2 /GF behaves as a superb and durable electrocatalyst for ambient NH3 generation via NO reduction in acids. It is capable of attaining a Faradaic efficiency of 76.6 % and a large NH3 yield of up to 99.6 μmol cm −2  h −1 . The MoS2 ‐based Zn‐NO battery delivers a power density of 1.04 mW cm −2 with an NH3 yield of 411.8 μg h −1  mgcat. −1 .